Assessment of biodiversity consideration in the carbon budgets process - Jarmain, C.; Byrne, K.A.; Daly, H.; Emmerson, M.; McKeon, C.; Moran, J.; Moriarty, R.; Styles, D.; Buckley, Y.M.; Buckley, Y.M. (Climate Change Advisory Council, 2024)
For Ireland to achieve its ambitious carbon budget targets to reduce greenhouse gas emissions, significant changes of land and sea use are necessary over the coming years. The required changes, particularly in the agriculture, energy and forestry sectors, will have implications for the health and condition of habitats and the spatial distribution of species. This report was developed to address the need to consider impacts to biodiversity in achieving the carbon budgets targets and to make recommendations on how best to incorporate biodiversity in this process. The report outlines the main policy frameworks for climate action and biodiversity protection and restoration in Ireland. An analysis of trade-offs, synergies and lose-lose scenarios is provided for climate and biodiversity actions mandated by the different policy frameworks. This analysis is provided for different land use categories as a basis for assessing risks and to identify appropriate risk mitigation measures. The report emphasizes the need to achieve statutory obligations for biodiversity protection and restoration and align policies and targets for both climate and biodiversity. It calls for the development of a national integrated land use strategy to inform on the ground actions and for this strategy to be underpinned by a spatial planning framework as impacts on biodiversity are highly context and location specific. The report highlights the importance of the increased adoption of nature-friendly forestry and farming practices and the appropriate siting of renewable energy infrastructures in achieving land use change for climate and biodiversity benefits. The report also identifies the need to define the meaning of the climate neutrality and biodiversity rich aspects of the national climate objective. Lastly, it states that Ireland should avoid contributing to biodiversity and carbon decline in other countries.
PUBLISHED
Relevant to the recommendation of the Climate Change Advisory Council to government on carbon budgets.
Keywords: Smart & Sustainable Planet